Heat transfer augmentation by helically twisted tapes as swirl and turbulence promoters - Eiamsa-ard, S.; Yongsiri, K.; Nanan, K.; Thianpong, C. (My University, 2012)
This paper describes heat transfer enhancement attributed to helically twisted tapes (HTTs). Each helically twisted tape was fabricated by twisting a straight tape to form a typical twisted tape then bending the twisted tape into a helical shape. The experiments were performed using HTTs with three twist ratios (y/. W) of 2, 2.5 and 3, three helical pitch ratios (p/. D) of 1, 1.5 and 2 for Reynolds number between 6000 and 20,000. The conventional helical tape (CHT) was also tested for comparison. The obtained results reveal that at similar conditions (y/. W and . p/. D), HTTs give lower Nusselt number and friction but higher thermal performance factor than CHTs. Heat transfer rate and friction factor increase as the tape twist ratio and helical pitch ratio decrease, while the thermal performance shows opposite trend. In the present range, the highest thermal performance factor of 1.29 is achieved by utilizing the tape with the largest twist ratio (y/. W=3) and helical pitch ratio (p/. D=2) at Reynolds number of 6000. © 2012 Elsevier B.V.
Keywords: Heat exchanger; Heat transfer enhancement; Helically twisted tape; Swirl; Turbulence